Reconstruction of the Prophet's Maulid Tradition in the Palembang Malay Community - Niswah, Choirun; Izomiddin, Izomiddin; Azwar, Alfi Julizun; Bety, Bety; Choiriyah, Choiriyah (Dialogia, 2023)
This research aims to discover the dynamics of the Maulid Nabi tradition, reconstruction, and analysis of the phenomenology of the reconstruction of the Maulid Nabi tradition in Palembang Malay Society. This study uses a reformistic typology (renewal) with a phenomenologically reconstructive approach assisted by anthropology and history—data collection by in-depth interviews and observation. The results of the study show that there are five variants in the implementation of the Maulid Nabi tradition. First, the annual tradition of not reading the Mawlid book. Second, the annual tradition of reading the Maulid book. Third, Maulid Arbain and Isyrin. Fourth, Mawlid Twelve Nights of Mawlid. Fifth, as a weekly wirid. Even though it is done differently, the substance shows love for the Prophet Muhammad. Reconstruction was carried out in the five variants. The Maulid Nabi tradition is an established tradition carried out from generation to generation while maintaining character and characteristics in terms of objectives, intentions or motivations, values, theological foundations, the position of the Prophet as uswatun hasanah, recitation of blessings and mahal al-qiyām. Reconstruction of the Maulid Nabi tradition in the Palembang Malay community carries a theological meaning. The Palembang Malay community must be reintroduced to sunnatullah theology. Second, social, which includes aspects of togetherness. Third, psychology is evident at the time of expensive al-qiyām. The congregation must understand the meaning in aspects related to the Mawlid tradition rationally, not only in the physical meaning.